GEMBALAKANLAH DOMBA-DOMBA-KU: Peningkatan Kompetensi Pelayanan melalui pemahaman kembali “Poda Tohonan Hasintuaon” di HKBP Se Ressort Tanjung Balai Kabupaten Asahan - Pahala Jannen Simanjuntak; Parlaungan Christopel Simanjuntak; Frans Julu Sianturi (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2024)
Church ministers must continually refresh (mangarataratai) and renew their ministry (ulaon hasintuaon) to maintain its quality and ensure it leads in a positive direction. This renewal is essential because, like cell phones that need recharging or plants that require watering to grow and bear fruit, church servants also need regular spiritual and professional refreshment to remain effective in their calling. While ministers are chosen and dedicated to advancing God’s kingdom, they often encounter challenges that highlight their human frailty. Despite these challenges, faith in the empowering presence of God through Jesus Christ sustains and strengthens them. This article reports on a community service initiative (PKM) conducted at HKBP Suka Maju, involving the entire church assembly of the Tanjung Balai Resort. The initiative, through training and lectures, sought to deepen the assembly members’ appreciation of their calling and their commitment to serving as members of the HKBP church. The program emphasized alignment with HKBP church documents, which are firmly grounded in the Bible as God’s Word. Keywords: Assembly, HKBP Church, HKBP Documents, Bible